Earthquake Sequence Dynamics at the Interface Between an Elastic Layer and Underlying Half‐Space in Antiplane Shear. Issue 12 (10th December 2020) - Abrahams, Lauren S.; Allison, Kali L.; Dunham, Eric M.
Abstract: We quantify sliding stability and rupture styles for a horizontal interface between an elastic layer and stiffer elastic half‐space with a free surface on top and rate‐and‐state friction on the interface. This geometry includes shallowly dipping subduction zones, landslides, and ice streams. Specific motivation comes from quasiperiodic slow slip events on the Whillans Ice Plain in West Antarctica. We quantify the influence of layer thickness on sliding stability, specifically whether a steadily loaded system produces steady sliding or stick‐slip sequences. We do this using both linear stability analysis and nonlinear earthquake sequence simulations. We restrict our attention to the 2‐D antiplane shear problem but anticipate that our findings generalize to more complex 2‐D in‐plane and 3‐D problems. Steady sliding with velocity‐weakening rate‐and‐state friction is linearly unstable to Fourier mode perturbations having wavelengths greater than a critical wavelength ( λ c ). We quantify the dependence of λ c on the rate‐and‐state friction parameters, elastic properties, loading, and the layer thickness ( H ). Confirming previous studies, we find that λ c ∝ H 1/2 for small H and is independent of H for large H . The linear stability analysis provides insight into nonlinear earthquake sequence dynamics of a nominally velocity‐strengthening interface containing a velocity‐weakening region of width W . Sequence simulations reveal a transition from steady sliding at small W to stick‐slip events when W exceeds a critical width ( W c r ), with W c r ∝ H 1/2 for small H . Overall, this study demonstrates that the reduced stiffness of thin layers promotes instability, with implications for sliding dynamics in thin layer geometries. Key Points: We quantified sliding stability of an elastic layer over a stiffer half‐space with rate‐and‐state friction at the interface Reduced stiffness of thin layers with a free surface on top promotes instability The linear stability analysis explains conditions for the onset of slow slip sequences